The role of coffee-based Agroforestry in improving food security through dietary diversification - Beshea Abdissa Chemeda; Feyera Senbeta Wakjira; Emiru Birhane (Discover Agriculture)
Abstract Agroforestry systems enhance ecosystem services, which helps decrease food insecurity. There is limited evidence addressing its importance in improving food security and diversity despite the recognized benefits of agroforestry. This study was conducted to examine how coffee-based agroforestry systems improved food security through diversified crop production in the agroforestry system in Gimbi district, West Wollega, Ethiopia. A multi-stage sampling procedure was used to select 402 sample households. Data were collected through household surveys, focus group discussions (FGDs), and key informant interviews. Household Dietary Diversity Score (HDDS), based on a 24 h recall period and Household Food Insecurity Access Score (HFIAS) measurements were used to evaluate the impact of crop diversity on the status of food security of the household coffee farmers. The coffee-based agroforestry system management helped farmers to produce various types of fruits, vegetables, cereals, and other crops, leading to a diversified diet year-round. The average dietary diversity score of household heads was 4.4 ± 1.27. About 34.33% of the sampled households had low, 45.77% had medium, and 19.90% had high dietary diversity. All farmers consumed cereal crops during the 24 h recall period, followed by condiments, beans, and vegetables. The household head’s age, education, annual income, agroforestry practices, and tropical livestock units influenced the household's dietary diversity positively and significantly. Distance to the nearest market was negatively associated with dietary diversity. The study underscores the potential of coffee-based agroforestry as a sustainable agricultural practice that can enhance food security through crop diversification. Policymakers are encouraged to promote agroforestry systems through supportive policies, extension services, and market access initiatives to improve dietary diversity and resilience among smallholder farmers.